Analysis of Water & Sanitation Hygiene Problems During Flood Disaster in Sei Serindan Village, Sei Kepayang District, Asahan Regency - Susilawati, Susilawati; Gunawan, Amanda Natasya; Hanafi, Riski Aditia; Hanifa, Nazwa Ihza; Faiza, Mayla (PROMOTOR, 2025)
Floods that often hit Sei Serindan Village, Sei Kepayang District, Asahan Regency, cause various problems related to clean water quality and sanitation. This study aims to analyze the impact of flood disasters on water quality, cleanliness, and sanitation and their effects on public health. The method used is qualitative descriptive research with a case study approach, through in-depth interviews with Village Heads, Hamlet Heads, and field observations. The results of the study showed that floods occur every year with a long duration, which causes pollution of water sources by waste and dirt. A total of 1,072 heads of families (70%) still use water with poor quality and have personal hygiene problems, while 460 heads of families (30%) already use clean water and have good personal hygiene. This difference is caused by economic factors, where middle to low-income families rely on polluted river water, even though they have made filtering efforts. Meanwhile, middle to high-income families have used PAM water. Although the community has used healthy toilets, floods cause waste management problems and pile up of garbage, which results in dirty environmental conditions and an increase in skin diseases such as scabies. The village government does not yet have a structured program for flood disaster management and clean water quality improvement. This study recommends the need for more attention from local and central governments to provide effective programs in dealing with clean water and sanitation problems in disaster-prone areas.